A Study on Appearance Checks for Structures with UAV-Based Spatial Imagery Information - Moon Kim, Dong; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is difficult to do visual inspections and checks for safety assessment in structures with low accessibility. This study, thus, set out to explore the possibilities of inspecting structure appearances with a UAV(Unmanned Aerial Vehicle)-based image information acquisition system.Methods/Statistical analysis: Aerial photogrammetry was done with a UAV equipped datum point survey and image photography functions to produce spatial imagery information. The imagery information that was acquired was produced into ortho-photos and compiled as spatial imagery information based on the datum point information. Preprocessing and image analysis (edge extraction) techniques were applied to spatial imagery information to extract cracks in a structure.Findings: In the survey of ground control points, which have the biggest impacts on the spatial accuracy of spatial imagery information, location accuracy was very good at 0.027m, 0.051m, and 0.106m on the X, Y, and H coordinates, respectively. As an image analysis technique for spatial imagery information, the Canny Image Detection technique was applied to extract 13 risk elements. Compared with on-site visual inspection, it succeeded in detecting 100% of the scaling and wire & cable except for micro-cracks and white rusts, which have no influence on the structural damage of general structures. The geometric forms of cracks detected under the category of cracks were defined with diagonal and perpendicular lines. The cracks were an average of 0.6mm in width and an average of 569mm in length, recording the minimum 301mm and maximum 739mm in length.Improvements/Applications: The findings show that the UAV-based imagery information acquisition system helped to check and evaluate cracked parts in structures with low accessibility and was expected to serve effectively in the compilation of 3D spatial information as well as the inspection of structural appearance.